Organic Diamine‐Regulated Vanadium Oxides as Cathode Materials for High‐Performance Sodium Ion Batteries - Han, Xu; Qiu, Tianyu; Li, Meiwei; Du, Jing; Tang, Wensi; Cheng, Sihang; Yao, Ruiqi; Li, Yingqi; Tan, Huaqiao; Wang, Yonghui; Li, Yangguang (Advanced functional materials, 2023)
Pre‐intercalating ions between VO layers is considered to be an effective strategy to modulate the interlayer spacing of 2D vanadium oxides. However, the rigid pre‐intercalated ions hardly keep stable during repeated charging/discharging process and their sizes limit the extent of interlayer spacing expansion, which inevitably lead to poor rate capability and cycle stability. In this work, aliphatic diamines are adopted as pre‐intercalated guests to elastically modulate the interlayer spacing of VO layers by tuning the chain length of the organic diamine molecules. Benefiting from the strong interaction between the terminal doubly protonated amine and the polar negative oxygen bridge of the VO layers, the aliphatic diamine molecules can act as a structural stabilizer between the layers and boost fast Na ion diffusion (10 −8 to 10 −10 cm 2 s −1 ). The sodium ion battery based on the first synthesized 1,6‐hexanediamine pre‐intercalated vanadium oxide supported on nickel foam hybrid cathode achieves a large specific capacity of 597 mAh g −1 at 0.09 A g −1 , as well as superior rate performance and cycling stability. This work provides a strategy to elastically modulate 2D layered materials with tunable interlayer spacing for batteries based on large‐size‐ions.